-4b-b=-8b-12

Simple and best practice solution for -4b-b=-8b-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4b-b=-8b-12 equation:



-4b-b=-8b-12
We move all terms to the left:
-4b-b-(-8b-12)=0
We add all the numbers together, and all the variables
-5b-(-8b-12)=0
We get rid of parentheses
-5b+8b+12=0
We add all the numbers together, and all the variables
3b+12=0
We move all terms containing b to the left, all other terms to the right
3b=-12
b=-12/3
b=-4

See similar equations:

| 8(x+9)+4=11x-3(x-6) | | 15f-19=20+18f+18 | | .56m-10)=3m-5 | | -16y+13=-7-17y | | 2x-10=8x+14 | | 10-4(3-2y)=8y5 | | 2(2t+4)=0.75(24-8t | | 8x+4=143 | | 14=-10k+3k | | 5x+6=-6+2x+24 | | 7+a➗3=5 | | 12x=6=3x-12 | | 7x+5=10x+2-3x | | 5x+10+72=360 | | -6+4x=3+8x-9 | | -4+3x=2+2x | | 5^2x+3*5^x+1=100 | | -8.34-12d=-11.4d | | 1/8(8x-7)=-1/7-8/7 | | -9=6x+7-2x | | -4x-2(2x+10)=-160 | | 3(b–4)+5b=44 | | -(x-2)+3x=14 | | 8+6a=-6+8a | | 3(r+4)-2r=-5 | | f(3)=2(3)(6)-4(3) | | 18x-9=4x+5 | | v+4/5=9/5 | | 4x-2x+7=-21 | | 4-10x=44 | | 11x+15=6x+70 | | 447+x=−261 |

Equations solver categories